GITA DUA BUDAYA - Sandra Syarif; Wimbrayardi Wimbrayardi; Syeilendra Syeilendra (SENDRATASIK UNP, 2013)
Abstract   The artwork Gita Dua Budaya was inspired by the life journey of its composer that was born in the family which has two different cultures. They are Minangkabau and Mandailing existed among modern and heterogenic society. This musical artwork was aimed at : (1) combining two traditional arts,  Minangkabau traditional art and Mandailing traditional art, that were generated from the traditional instruments of each culture and added by modern instruments. (2) raising love toward the traditional art of Minangkabau and Mandailing particularly for the young generations. (3) encouraging to do further study on traditional artworks in the archipelago. (4) Motivating the students of Drama, Dance and Music to find the positive experiences in improving the ability and the quality of playing music.   Kata kunci : Budaya, Kesenian, Mandailing, Minangkabau, Musik Tradisonal.